2017
DOI: 10.1371/journal.pone.0182324
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum thrombomodulin level is associated with disease severity and mortality in pediatric sepsis

Abstract: BackgroundEndothelial dysfunction plays an important role in the pathophysiology of sepsis. As previously reported, the serum thrombomodulin is elevated in diseases associated with endothelial injury.ObjectiveThe aim of this study was to investigate the association of serum thrombomodulin level in different pediatric sepsis syndromes and evaluate the relationship with disease severity and mortality.MethodsWe prospectively collected cases of sepsis treated in a pediatric intensive care unit from June 2012 to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…TM concentrations are also higher in lethal cases of sepsis than in surviving patients (Boldt et al 1995;Lin et al 2008). Serum thrombomodulin concentrations were found to be increased in different paediatric sepsis syndromes and were correlated with the severity and mortality of the disease (Lin et al 2017). In the present study, the concentration of plasma TM in calves with sepsis was significantly higher than in the control group (P < 0.01) ( Table 3).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…TM concentrations are also higher in lethal cases of sepsis than in surviving patients (Boldt et al 1995;Lin et al 2008). Serum thrombomodulin concentrations were found to be increased in different paediatric sepsis syndromes and were correlated with the severity and mortality of the disease (Lin et al 2017). In the present study, the concentration of plasma TM in calves with sepsis was significantly higher than in the control group (P < 0.01) ( Table 3).…”
Section: Discussionsupporting
confidence: 55%
“…Numerous studies have been conducted so far on the role of biomarkers such as TM and PTX3 in human patients with sepsis but there is no report on livestock. The studies conducted on humans and laboratory animals have identified elevated TM concentrations in conjunction with disease processes that cause haemostatic disorders and endothelial damage (Ohdama et al 1994;Wu et al 2016;Lin et al 2017). TM binds to highmobility group box 1 protein and thereby prevents activation of leucocytes under in vitro conditions and lipopolysaccharide-induced lethality under in vivo conditions (Abeyama et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences between thrombomodulin levels in type I and type II, which is in agreement with previous reports demonstrating high levels of soluble thrombomodulin in bacterial infections regardless of the causative microorganism (34,35). Moreover, elevated concentrations of thrombomodulin in blood have been reported in patients with sepsis (35)(36)(37)(38). Such elevated levels were also detected in the sepsis cohort we included during the validation stage.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, thrombomodulin retained its discriminatory power for NSTIs. Finally, thrombomodulin has also been proposed as a biomarker for the prediction of mortality in patients with sepsis ( 35 , 37 ) and septic shock ( 39 ). Although an association with mortality in NSTI was not noted in our study, a weak association with septic shock was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Another risk factor of 90-day mortality that emerged as particularly important for prediction was elevated thrombomodulin level. Thrombomodulin, an integral endothelial cell membrane protein, is cleaved and released into the bloodstream during sepsis and septic shock [26,27], leading to elevated levels of serum thrombomodulin in pediatric and adult sepsis patients [28,29]. Endothelium is the primary site of damage in sepsis due to massive production of proin ammatory cytokines [30].…”
Section: Discussionmentioning
confidence: 99%